(untitled) (International Seven Journal of Health Research, 2024)
Cardiorespiratory arrest (CRA) occurs when the heartbeat suddenly stops and can cause a variety of damages to the victim, such as irreversible neurological problems or even death, which is why it is crucial to take appropriate measures quickly. The aim of this study was to review the literature on the role of the nursing team in caring for a patient in cardiopulmonary arrest. The articles analyzed corresponded to the years 2010 to 2023, available in the following databases: Scientific Electronic Library Online (SCIELO), US National Library of Medicine (PUBMED), Virtual Health Library of the Ministry of Health (BVS) and Google Scholar. The following descriptors were used: Role of the nursing team AND Recovery OR Cardiopulmonary arrest, cardiac arrest AND cardiopulmonary resuscitation AND nursing. In accordance with the inclusion and exclusion criteria, nine articles were selected. In conclusion, this study has allowed us to highlight the importance of the nurse’s role in caring for victims of cardiac arrest, effectively identifying changes prior to or after the arrest, as well as symptoms and signs, intervening early and providing the necessary care.